Predation on Gonocephalus liogaster (Agamidae) by Ptyas carinata (Colubridae) in Sarawak, Borneo - Das, Indraneil; Wong, Jye Wen (Societas Europaea Herpetologica, 2021)
Gonocephalus liogaster (Günther, 1872) is a large, forest-dwelling lizard, inhabiting lowland rainforests and peat swamp forests of Sundaland (Das, 2006). They are often found perching on tree trunks during the day and sleep clinging onto slender tree branches, their heads directed towards the trunk at night. This sleeping behaviour is commonly seen in many arboreal lizards to enhance detecting and subsequently avoiding nocturnal predators (Mohanty et al., 2016). Despite these strategies, lizards are often mentioned as prey of snakes. Within the genus, G. chamaeleontinus (Laurenti, 1768) has been reported as prey of the cat snake, Boiga drapiezii (Boie, 1827) (Cegalerba and Szwemberg, n.d.) in Sumatra, Indonesia.